The Pink Tide and social policy agendas: the government platforms of the PSC h (2000) and the PT (2002) - Ribas, Beatriz de Paula Silva (FCL-UNESP Laboratório Editorial, 2018)
In this paper I propose an analysis of the social agenda of the government program of two Latin-American left-wing parties: the Socialist Party of Chile (PSCh) and the Workers’ Party (PT) in Brazil. Both were part of the so-called “Maré Rosa” or Pink Tide, a political phenomenon which brought about an electoral renewal and the victory of left-wing parties in elections for the executive branch in Latin America. The starting point of my analysis is the question: what are the similarities and the differences in the social agendas of these two parties between the years 2000 and 2002? We hypothesize that both parties were elected amid a crisis of democratic representation and the loss of legitimacy of mainstream parties as well as the party system during the “lost decade”. Both proposed a solution to this problem: augment social policies applicable to certain specific groups, taking into account the institutional and political heterogeneity of these interest groups.